2018
DOI: 10.1371/journal.pone.0204449
|View full text |Cite
|
Sign up to set email alerts
|

Intrarater and interrater agreement and reliability of vestibular evoked myogenic potential triggered by galvanic vestibular stimulation (galvanic-VEMP) for HTLV-1 associated myelopathy testing

Abstract: BackgroundThe vestibular evoked myogenic potential triggered by galvanic vestibular stimulation (galvanic-VEMP) has been used to assess the function of the vestibulospinal motor tract and is a candidate biomarker to predict and monitor the human T-cell lymphotropic virus type 1 (HTLV-1) associated myelopathy (HAM). This study determined the agreement and reliability of this exam.MethodsGalvanic-VEMP was performed in 96 participants, of which 24 patients presented HAM, 27 HTLV-1-asymptomatic carriers, and 45 HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…In accordance with the present study, previous studies have already shown that ML is the best component to discriminate changes since this peak is easier to define with the best intrarater and interrater agreement and presents the best area under the ROC curve comparing to SL (47)(48)(49). Conversely, SL can be often indistinguishable from the baseline and its measurement has presented the worst interrater correlation comparing to ML (45,(47)(48)(49).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In accordance with the present study, previous studies have already shown that ML is the best component to discriminate changes since this peak is easier to define with the best intrarater and interrater agreement and presents the best area under the ROC curve comparing to SL (47)(48)(49). Conversely, SL can be often indistinguishable from the baseline and its measurement has presented the worst interrater correlation comparing to ML (45,(47)(48)(49).…”
Section: Discussionsupporting
confidence: 90%
“…The changes in oVEMP have occurred only in HAM group, which indicates a midbrain involvement. This finding is precisely in accordance with the best knowledge about HAM physiopathology and reinforces the validity and accuracy of VEMP for clinical use (44)(45)(46)(47)(48)(49). In this study, the best contribution of VEMP in the evaluation of the HTLV-1 population was to the asymptomatic infection.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…They are the main responsible for voluntary motricity [19]. Recent studies [6,21,22] have pointed to the involvement of the spinal cord and the brain in the loss of postural control. The loss of postural control may have its origin in the suprasegmental system.…”
Section: Discussionmentioning
confidence: 99%
“…The subclinical spinal cord injury related to HAM has been already shown through VEMP of cervical and of lower limbs muscles, exams that are used to test the vestibulo-collic reflex [8,9,13,16,17]. The present study proposes the use of VEMP of the oculomotor system (ocular VEMP) to test the brainstem pathways associated with body balance to verify the extension of the HTLV-1-neurological damage.…”
Section: Introductionmentioning
confidence: 99%